Monetary policy effects : comparison between the U.S. and Australia. How do the interest rates influence the housing markets? - Truska, Jan; de Batz de Trenquelléon, Laure Sabine Marie; Zezula, Jakub; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis investigates the impact of central bank interest rates on key housing market indicators - average House prices, Average mortgage sizes, and total Home loan values - in the United States and Australia over a specified eight-year period. Using Pearson´s Correlation and Simple linear regression analyses, the study evaluates six dataset pairs comprising each country´s main policy interest rate (the U.S. Federal Funds Rate and the Australian Cash Rate) and the three chosen housing variables. The results reveal strong contrasts between the two countries. In Australia, all three analyses demonstrate a strong and consistent negative linear relationship, indicating that lower interest rates are closely associated with rising housing prices, mortgage sizes, and loan volumes. These findings align with traditional economic theory, suggesting a transparent and effective monetary transmission mechanism. In contrast, the U.S. data shows weaker and more varied results, with mostly moderate to weak positive correlations, contrary to theoretical expectations. This suggests that the influence of interest rates in the U.S. housing market is diluted by additional structural, economic, and institutional factors. The study concludes that monetary policy impacts on housing markets are highly context-dependent. It emphasizes the need for country-specific policy design and modelling that reflect the unique characteristics of each nation´s financial and housing systems.
Vedoucí práce: Laure Sabine Marie de Batz de Trenquelléon
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses